Estrategias didácticas para incentivar la expresión oral en los estudiantes del 4to año de EGB de la UE Emigdio Esparza Moreno, Babahoyo. 2022 - Vélez Salvatierra, Ana Consuelo (2022)
Didactic strategies are very important in education since they allow the transmission of educational content and make it more accessible to the student's understanding. In oral expression, the use of effective and innovative didactic activities contributes to the development of linguistic skills in students in such a way that they can communicate effectively. Reason for which, the objective of the present investigation was to strengthen oral expression through the application of didactic strategies to encourage communication in the students of the Fourth year of Basic Education of the Emigdio Esparza Moreno Educational Unit, Province of Los Ríos, Babahoyo Canton. The methodology implemented was non-experimental research, since the purpose is not to manipulate the study variables, but to analyze and describe the problematic situation. The types of research used are: documentary, field and descriptive; The population consisted of 152 students who are in the 4th year of Basic Education at the Emigdio Esparza Moreno Educational Unit, who belong to 4 parallels, A, B, C and D, and 4 teachers who teach at that academic level. The techniques applied were direct observation of the students and a survey of the teachers and the instruments said and observation and questionnaires of questions. The results of the investigation allowed us to conclude that one of the main causes for which infants have difficulties in oral expression is that the teaching staff does not apply enough didactic strategies to strengthen and increase the linguistic abilities of the students.